Short-term effects of transdermal estradiol in men undergoing androgen deprivation therapy for prostate cancer: a randomized placebo-controlled trial. Issue 5 (May 2018) - Russell, Nicholas; Hoermann, Rudolf; Cheung, Ada S; Ching, Michael; Zajac, Jeffrey D; Handelsman, David J; Grossmann, Mathis
Abstract : Objective: There is increasing recognition that, in men, some biological actions attributed to testosterone (TS) are mediated by estradiol (E2). This study used two low doses of daily transdermal E2 gel to assess the effects on circulating E2 concentrations in men with prostate cancer with suppressed endogenous E2 production arising from androgen deprivation therapy (ADT). Secondarily, we aimed to assess short-term biological effects of E2 add-back without increasing circulating TS. Design: 28-day randomised, placebo-controlled trial. Methods: 37 participants were randomised to either 0.9 or 1.8 mg of 0.1% E2 gel per day or matched placebo gel. Fasting morning serum hormones, quality of life questionnaires, and treatment side effects were evaluated at baseline, days 14 and 28. Hot flush diaries and other biochemical measurements were completed at baseline and study end. Results: Transdermal E2 significantly raised serum E2 from baseline to day 28 compared to placebo in the 0.9 mg dose group (median: 208 pmol/L; interquartile range: 157–332) and in the 1.8 mg dose group (median: 220 pmol/L; interquartile range: 144–660). E2 treatment reduced hot flush frequency and severity as well as beta carboxyl-terminal type 1 collagen telopeptide. Conclusion: In men with castrate levels of E2 and TS, daily transdermal E2: 0.9–1.8 mg increased median serum E2 concentrations into the reference range reported for healthy men, but with substantial variability. E2 treatment reduced hot flushes and bone resorption. Larger studies will be required to test whether low-dose E2 treatment can mitigate ADT-associated adverse effects without E2-related toxicity.